Walnut-structure Si–G/C materials with high coulombic efficiency for long-life lithium ion batteries. Issue 48 (2nd August 2018) - Xiao, Chengmao; He, Peng; Ren, Jianguo; Yue, Min; Huang, Youyuan; He, Xueqin
Abstract : Nano-sized silicon is a potential high energy density anode material for lithium ion batteries. Abstract : Nano-sized silicon is a potential high energy density anode material for lithium ion batteries. However, the practical use of a nano-Si anode is still challenging due to its low coulombic efficiency, poor scalability and cycling stability. Herein, a Si/graphite/carbon (Si–G/C) composite with a core–shell structure was fabricated by a facile two-step chemical process, stirring–evaporating followed by heat treatment. The composite structure consists of a graphite core, coated first by silicon and then amorphous carbon, which was decomposed by pitch. The as-prepared Si–G/C composite anode demonstrates a first cycle capacity of about 650 mA h g −1, over 90% coulombic efficiency, and high capacity retention of 96.7% after 50 cycles. When paired with a commercial NCA cathode, superior cycling stability with more than 81% capacity retention was achieved for 1200 cycles. These results demonstrate that such a core–shell Si–G/C composite is a promising anode material for high energy Li-ion batteries.